L’engagement civique des adolescents au prisme de leurs vlogues sur l’intimidation - Caroline Caron (Communication)
This article presents the findings of a grounded theory analysis of 55 anti-bullying vlogs produced by French-speaking Quebec teens and shown on YouTube between 2010 and 2014. It seeks to clarify the concept of online civic engagement by young people using an original methodological approach based on Gunther Kress’s social semiotics. The findings show that each vlog is part of a chain of invitations and responses, therefore producing a youth-friendly social semiotic space created by and for young people. In this space, civic engagement takes the form of discursive participation, which is achieved through the semiotic work of the vloggers.